The Effect of Emotional Intelligence, Creativity, And Digital Technology Utilization on The Performance of Young Entrepreneurs - Rohali, Alya; Hardiansyah, Rian (Al-Qalam Institue, 2026)
This study aims to examine the effect of emotional intelligence, creativity, and digital technology utilization on young entrepreneurs’ performance. A quantitative explanatory approach was employed to investigate the causal relationships among the variables. The research involved 93 young entrepreneurs as respondents, selected using the Slovin formula from a total population of 1,362 business units. Data were collected through structured questionnaires using a Likert scale and analyzed using multiple linear regression with SPSS version 26. The results indicate that emotional intelligence, creativity, and digital technology utilization positively and significantly influence young entrepreneurs’ performance, both individually and simultaneously. These findings highlight that emotional regulation, innovative thinking, and digital literacy are key determinants of business productivity and competitiveness. The study provides theoretical contributions by integrating psychological, creative, and technological perspectives in entrepreneurship research. Practically, it offers guidance for policymakers and stakeholders in designing strategies to enhance the capabilities of young entrepreneurs and strengthen their performance in the digital era.